OPTIMALISASI METODE BLADE TURBIN ANGIN SUMBU HORIZONTAL - Fathur Rahman; Ika Nurjannah; Handini Novita Sari; Alexander Christian; Muhammad Khoirul Hidayat (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2023)
The utilization of wind turbines is able to convert wind energy into electrical energy. It is recorded from the DG of NREEC source that Indonesia has a wind energy potential of 60.6 Giga Watt (GW) with a total renewable energy potential of 442GW. One of the most common types of wind turbines is the horizontal axis wind turbine. This study uses a literature study method that aims to compare and summarize data optimizing variations in the number of blades and wind speed on horizontal axis wind turbines from various sources. The results of the study are known that the pinwheel power generated by the rotation of the pinwheel blade produces energy that is converted into electrical energy. The wind speed and blade rotation yield are directly proportional to the energy produced. The greater the wind speed given to the turbine, the higher the rotation. Variations in the number of blades result in variations in rotational properties, since the effect of the ratio of tip speed is inversely proportional to wind speed. The performance of horizontal axis wind turbines can be optimized by applying blade design using chord and twist linearization methods. The greatest efficiency of the counter-rotational horizontal shaft wind turbine is achieved at a blade angle of 10° and a wind speed of 4.03m/s, resulting in a maximum efficiency of up to 71.8%, which is higher than the optimal single-rotor power coefficient of 59%. This means dual-rotor wind turbines are more efficient at converting energy than single-rotor wind turbines.